As letras da lei x As leis das letras: exames de capacidade profissional e a instrução pública na Província do Ceará (1856-1888) - Dantas, Elza Alves (2010)
This work investigates, through the exams of Professional Capacity, different subject matters relevant to primary teaching. It has been begun for understanding the primary teaching, the teachers and the ways of the process of selection of the public teaching. It has discussing the construction of the contents as the forms as the teachers expressed themselves in their exams. It has pointed the problems out of the writing of the History in the XIX century, the teaching in your relation with sphere of moral and religion, and the punishment of the school.